PANCREATIC ISLET TRANSPLANTATION IN THE TREATMENT OF TYPE I DIABETES - Aleksandra Kasprzyk; Klaudia Wilk; Edyta Witkowska; Marcin Ciechański; Szymon Cholewiński; Bernadetta Wilk; Piotr Stachura; Piotr Rejman; Katarzyna Pszczoła; Katarzyna Jurkiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Type I diabetes is a chronic autoimmune disease characterized by a complete lack of insulin secretion due to damage to pancreatic beta cells. Despite the development of new methods of glycemic monitoring and intensive insulin therapy, traditional treatment does not lead to a complete cure, and therefore does not completely rule out the occurrence of complications such as hyper- or hypoglycemia. An unconventional therapeutic method is pancreatic islet transplantation, which makes it possible to restore the physiological secretion of insulin by the pancreas. This article presents the history of the development of islet transplantation and reviews the latest discoveries regarding the technique of islet isolation and transplantation, current transplant sites, and the difficulties associated with donor shortages and immunosuppression. Also discussed are ways to improve the survival and function of transplanted islets, which include the use of mesenchymal stem cells, encapsulation techniques and Treg lymphocytes. Special attention is given to research on insulin-producing cells derived from human pluripotent stem cells, and the results of clinical trials demonstrating the benefits of this method in reducing the risk of hypoglycemia and increasing metabolic control are summarized. Failures associated with achieving incomplete independence from exogenous insulin are also discussed. Pancreatic islet transplantation remains a promising, albeit still experimental, treatment for type I diabetes, requiring further research and refinement.Materials and Methods: This article presents a comprehensive review of literature derived from the PubMed database, encompassing studies published between 2018 and 2025.